2009
DOI: 10.1080/07373930903221739
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Wheat Drying in Thin Layer and Mathematical Simulation of a Fixed-Bed Convective Dryer

Abstract: Drying of wheat (Algerian cultivar: Hadba03) in thin layers was studied and mass flux phenomenon was used to characterize the thin-layer drying process. Thin-layer drying of wheat was determined for drying air temperature range of 40-60 C, relative humidity of drying air from 10 to 30%, air velocity of 0.7 m/s, and initial grain moisture from 26 to 31% (dry basis). Equilibrium moisture content of wheat was determined using desorption isotherms obtained from the thin-layer drying data. An equilibrium model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Many authors [3,4,5,6,7,8,9,10,11,12] have observed in agricultural products the absence of constant drying rate stage as well as a decrease on this rate value starting from the initial drying process. These results indicate that the material surface is not initially saturated with water, and the rate of internal moisture movement controls the drying rate during most of the process [13] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many authors [3,4,5,6,7,8,9,10,11,12] have observed in agricultural products the absence of constant drying rate stage as well as a decrease on this rate value starting from the initial drying process. These results indicate that the material surface is not initially saturated with water, and the rate of internal moisture movement controls the drying rate during most of the process [13] .…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have also revealed that air temperature has strong influence on drying rates enhancing their values [3,4,5,6,7,8,9,10,11,12,15,16,17,18] . However, drying processes at high temperatures can deteriorate the product quality by increasing temperature and moisture gradient leading to internal tensions, cracks, breakages, and fractures in the grain [16] .…”
Section: Introductionmentioning
confidence: 98%
“…Mathematical models of convective drying of wheat were reported by Aregba et al (2006). Hemis et al (2009) used a coupled heat and mass transfer model for the prediction of drying characteristics of wheat under convective air drying. The MW drying model which was developed by Campanone et al (2001Campanone et al ( , 2005 was used by Hemis et al (2011) for wheat seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the validity of the deep-bed drying model is directly dependent on how accurately the thin layer drying kinetics behaved [11][12][13]. Celma et al [14] examined the thin-layer drying behavior of sludge at air temperature range of 20-80°C and air velocity of 1 m s À1 .…”
Section: Introductionmentioning
confidence: 98%